2009
DOI: 10.1002/hep.23215
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine triphosphatase pontin is overexpressed in hepatocellular carcinoma and coregulated with reptin through a new posttranslational mechanism†

Abstract: Reptin and Pontin are related ATPases associated with stoichiometric amounts in several complexes involved in chromatin remodeling, transcriptional regulation, and telomerase activity. We found that Reptin was up-regulated in hepatocellular carcinoma (HCC) and that down-regulation of Reptin led to growth arrest. We show here that Pontin messenger RNA (mRNA) is also up-regulated in human HCC 3.9-fold as compared to nontumor liver (P ‫؍‬ 0.0004). Pontin expression was a strong independent factor of poor prognosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
68
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 57 publications
(81 citation statements)
references
References 36 publications
11
68
2
Order By: Relevance
“…With the aim of determining the role of Reptin ATPase activity in hepatocellular carcinoma cell growth, we first expressed the ATPase dead mutant D299N in the presence of endogenous Reptin, using lentiviral vectors. In agreement with our previous results showing a tight posttranslational control of Reptin expression (20), this strategy did not allow for an overexpression of Flag-tagged Reptin, either WT or mutated. Indeed, the total amount of Reptin was similar between the 3 conditions, with Flag-tagged Reptin representing approximately 50% of the total amount in transduced cells (Fig.…”
Section: Expression Of a Reptin Atpase-dead Mutant Impairs Hepatocellsupporting
confidence: 91%
See 4 more Smart Citations
“…With the aim of determining the role of Reptin ATPase activity in hepatocellular carcinoma cell growth, we first expressed the ATPase dead mutant D299N in the presence of endogenous Reptin, using lentiviral vectors. In agreement with our previous results showing a tight posttranslational control of Reptin expression (20), this strategy did not allow for an overexpression of Flag-tagged Reptin, either WT or mutated. Indeed, the total amount of Reptin was similar between the 3 conditions, with Flag-tagged Reptin representing approximately 50% of the total amount in transduced cells (Fig.…”
Section: Expression Of a Reptin Atpase-dead Mutant Impairs Hepatocellsupporting
confidence: 91%
“…Reptin mutants retained the same subcellular distribution as WT Reptin, and also their ability to partner with Pontin, suggesting that they had no gross defects besides the loss of ATPase activity that could explain their phenotypic effects. We and others have previously shown that Reptin silencing induced the codepletion of Pontin, via a posttranslational mechanism (4,7,20). However, we show here that cells reconstituted with the Reptin Walker B mutants expressed normal levels of Pontin such as those reconstituted with WT siRNA-resistant Reptin (20), thus ruling out that some of the effects seen with the mutants might be due to the loss of Pontin.…”
Section: Discussioncontrasting
confidence: 66%
See 3 more Smart Citations